Conceptual bases of preparation of the teacher of the fine arts at various steps of education (by the example of Khmelniskiy humanitarian-pedagogical academy) (Pedagogy of Higher and Secondary Education, 2006)
In article conceptual bases of preparation of experts of the fine arts in the supreme pedagogical educational institutions in modem conditions of development of education are opened and determined.
Keywords: cultural preparation; higher education; improvement of system of vocational training